2015
DOI: 10.1111/ggi.12661
|View full text |Cite
|
Sign up to set email alerts
|

White matter integrity and cognitive dysfunction: Radiological and neuropsychological correlations

Abstract: Cerebral white matter (WM) is comprised of nerve fibers interconnecting neurons in the cerebral cortex or the deep structures. With advancing age, WM frequently shows hyperintense lesions in T2-weighted or fluid-attenuated inversion recovery images in both the periventricular and deep WM. Patients with these WM lesions might manifest a variety of symptoms, such as parkinsonism, cognitive impairment, depression and apathy, when these WM lesions become sufficiently confluent and diffuse. However, there are incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 65 publications
3
32
0
Order By: Relevance
“…WMH volume increased markedly with aging, particularly in the frontal lobe in patients aged 75 years and over who were in the AD/aMCI cohort ( Ogama et al, 2016 ). The pathogenesis of WMH is most likely driven by ischemia resulting from hypertensive small vessel disease, but amyloid angiopathy may also be another underlying cause of extensive WMH ( Tomimoto, 2015 ). More recently, carriage of the apolipoprotein E4 genotype was reported to affect the relationship between glucose alterations and WMH ( Livny et al, 2016 ; Cox et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…WMH volume increased markedly with aging, particularly in the frontal lobe in patients aged 75 years and over who were in the AD/aMCI cohort ( Ogama et al, 2016 ). The pathogenesis of WMH is most likely driven by ischemia resulting from hypertensive small vessel disease, but amyloid angiopathy may also be another underlying cause of extensive WMH ( Tomimoto, 2015 ). More recently, carriage of the apolipoprotein E4 genotype was reported to affect the relationship between glucose alterations and WMH ( Livny et al, 2016 ; Cox et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…WMH are associated with white matter atrophy and cortical thinning ( Wardlaw et al, 2015 ). Importantly, WMH in AD patients involves both vascular changes and neurodegenerative mechanisms ( Tomimoto, 2015 ). Thus, it is necessary to separately measure gray and white matter volume to assess the burden of WMH in AD brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that the WMH posterior volume was larger than the anterior volume ( 56 58 ) in patients with cerebral amyloid angiopathy (CAA) as well as AD ( 59 ). CAA induces cerebral hypoperfusion in the white matter as a result of amyloid β deposition in the microvessels of the cerebral cortices and is found in more than 80% of all patients with AD ( 60 ). It is, therefore, likely that most patients in our cohort had comorbid CAA.…”
Section: Discussionmentioning
confidence: 99%